Using Dialect Discovery Worksheets to Learn About Children's Linguistic Strengths and Weaknesses - Moland, Christy Wynn; Oetting, Janna B. (Seminars in Speech and Language, 2025)
Dialect discovery worksheets focus on children's dialect-appropriate form productivity and sensitivity to linguistic context within a dialect. Focusing on tense and agreement (T/A) forms in African American English (AAE), we demonstrate how these worksheets can be used to reveal grammar strengths in children with typical development (TD) and grammar weaknesses in those with developmental language disorder (DLD).The participants were four kindergartners who spoke AAE (two males and two females; two DLD; two TD). The data were archival and came from an elicitation task. Using the worksheets, we categorized and quantified the participant's T/A dialect-general overt forms, dialect-specific overt forms, and zero forms by linguistic context.The TD participants demonstrated form productivity, producing significant numbers of T/A dialect-general overt, dialect-specific overt, and zero forms. They also varied their overt forms and zero forms in ways that demonstrated sensitivity to linguistic context. Those with DLD did not demonstrate form productivity, and they lacked variation in form use by linguistic context.Dialect discovery worksheets provide useful information about children's grammar systems within the context of their dialect(s). These worksheets should be considered for clinical practice and preprofessional student training.
Keywords: African American English; assessment; treatment; DLD